1988-1989 ネン エレバス カザン ノ コクサイ キョウドウ カンソク - 神沼, 克伊; カミヌマ, カツタダ; Kaminuma, Katsutada (1989)
P(論文) 1988-1989年の南極の夏シーズン, ニュージーランドとの国際共同観測で実施している「エレバス火山国際噴火機構の研究(IMEEMS : International Mount Erebus Eruption Mechanism Study)」に参加した。IMEEMSの大きな目的はエレバス火山(77.5°S, 167°E, 3794m)の山体内での地震観測と, 山頂火口縁にTVカメラを設置して火口からの噴火を実時間でスコット基地に送り, モニターとビデオ記録することである。これにより, 爆発の瞬間の時刻が決定でき, 同時に発生する地震と対応させることができる。日本はこれまでどおり, スコット基地に設置してあるレコーダー類の保守, 点検, 記録の整理などを分担した。1988年12月, エレバス火山の地震活動は前年同様に低かった。噴火は12月後半の16日間にTVモニター上で35回記録された。エレバス山の火山活動は全体に前年と同じ程度であった。 A program to continuously monitor the seismic activity of Mount Erebus (77.5°S, 167°E, 3794m) in Antarctica and to identify the mechanism of its eruption has been continued since January 1987 as an international cooperation between New Zealand and Japan, named IMEEMS (International Mount Erebus Eruption Mechanism Study). A TV camcra for monitoring explosions from the lava lake in the summit crater was installed at the crater rim of Mount Erebus. The video signals were transmitted to Scott Base of New Zealand by radio-telemetry and the exact time of eruptions was recorded using the same time code of the seismic network. A Japanese scientist participating in the IMEEMS visited Scott Base in December 1988 and conducted a series of observations of seismic and video recordings. The volcanic activities of Mount Erebus in December 1988 were nearly in the same situation for the last few seasons. departmental bulletin paper